2020
DOI: 10.1002/ijc.32943
|View full text |Cite
|
Sign up to set email alerts
|

Defects in long‐chain 3‐hydroxy acyl‐CoA dehydrogenase lead to hepatocellular carcinoma: A novel etiology of hepatocellular carcinoma

Abstract: The incidence of both nonalcoholic fatty liver disease (NAFLD) and hepatocellular carcinoma (HCC) have been increasing at an alarming rate. Little is known about NAFLD without cirrhosis as a risk for HCC. Here we report, for the first time, generation of a mouse model with a defect in long-chain 3-hydoxy acyl-CoA dehydrogenase (LCHAD). The LCHAD exon 15 deletion was embryonic lethal to the homozygous mice whereas heterozygous mice (HT) develop significant hepatic steatosis starting at young age (3 months old) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…HADHA, a fatty acid β-oxidation-related factor, mediates lipid programming to regulate multiple cellular programs, such as apoptosis, fat metabolism and mitochondrial function 26 , 44 , 45 , 46 , 47 . Increasing research has shown the important role of HADHA in metabolic dysfunction in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…HADHA, a fatty acid β-oxidation-related factor, mediates lipid programming to regulate multiple cellular programs, such as apoptosis, fat metabolism and mitochondrial function 26 , 44 , 45 , 46 , 47 . Increasing research has shown the important role of HADHA in metabolic dysfunction in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…in a model of oral cancer, HadHB is expressed at low levels (21); HadHa is a TSG in esophageal cancer (26) and Bc (58) and HadHB is a TSG in crc (44). HadHa is one of the liver cancer models and HadHa is expressed at low levels (29). in 11 organs, the HadH is involved in fatty acid oxidation and located in 2p23 (70).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that HadHa is associated with tumor differentiation and altered fatty acid β-oxidation. To verify that fatty acid β-oxidation disorder is associated with the development of hepatocellular carcinoma (Hcc) without cirrhosis, Khare et al (29) established a new mouse model. The study revealed that a mouse model deficient in long-chain 3-hydroxyacyl-coa dehydrogenase (lcHad) developed Hcc at an early age and demonstrated altered expression of early cancer markers.…”
Section: The Roles Of Hadh In Different Organsmentioning
confidence: 99%
“…Early studies suggested that defects in mitochondrial energy metabolism might underlay the skeletal muscle defects, and this has been supported by in vitro studies with mitochondria isolated from rat skeletal muscle [173][174][175]. Homozygote Hadha KO mice with exon 15 deletion are reported to result in either early postnatal or embryonic lethality, while heterozygosity leads to hepatic steatosis at a young age (3 months) and hepatocellular carcinoma without cirrhosis at an older age (>13 months) [70,176].…”
Section: Salla Disease (Sd)mentioning
confidence: 96%